Study report on Indian agriculture with IoT - G. Balakrishna; Nageswara Rao Moparthi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Most of the population of our country are depends on agriculture for their survival. Agriculture plays an important role in our country economy. But since past few years production from agriculture sector is decreasing drastically. Agriculture sector saw a drastic downfall in its productivity from past few years, there are many reasons for this downfall. In this paper we will discuss about past, present and future of agriculture in our country, agricultural policies which are provided by government to improve the growth of agriculture and reasons why we are not able see the growth in agriculture. And also we will see how can we adopt automation into agriculture using various emerging technologies like IoT (Internet of Things), data mining, cloud computing and machine learning and some authors done some quality work previously on this topic we will discuss that also. Here we will see previous work done by various authors which can be useful to increase the productivity of agriculture sector